2019
DOI: 10.3390/medicina55070317
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Dual Oxidase Upregulation in Rat Heart Tissues: Protective Effect of Melatonin

Abstract: Background: Radiation-induced heart injury can lead to increased risk of heart failure, attack, and ischemia. Some studies proposed IL-4 and IL-13 as two important cytokines that are involved in late effects of ionizing radiation. On the other hand, these cytokines may, through upregulation of Duox1 and Duox2, induce chronic oxidative stress, inflammation, and fibrosis. In this study, we evaluated the upregulation of Duox1 and Duox2 pathways in hearts following chest irradiation in rats and then detected possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The abnormal upregulation of these enzymes may lead to the destruction of normal function and the increase of oxidative damage [62]. Chronic oxidative stress and inflammation can lead to fibrosis and hypertrophy, which may undermine normal cardiac function and myocardial blood supply [63]. A study by Farhood et al in 2017 showed that irradiation increased the level of IL-4 but not the level of IL-13 in rats.…”
Section: Igf-1 and Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…The abnormal upregulation of these enzymes may lead to the destruction of normal function and the increase of oxidative damage [62]. Chronic oxidative stress and inflammation can lead to fibrosis and hypertrophy, which may undermine normal cardiac function and myocardial blood supply [63]. A study by Farhood et al in 2017 showed that irradiation increased the level of IL-4 but not the level of IL-13 in rats.…”
Section: Igf-1 and Oxidative Stressmentioning
confidence: 99%
“…The results of real-time PCR showed that radiation induced the upregulation of IL4ra1 (IL-4 receptor), DUOX1, and DUOX2; the changes induced by IL4ra1 and DUOX1 were the most obvious [62]. In addition to DUOX1 and DUOX2, IL-4 can also induce the upregulation of TGF-β, a powerful stimulator of fibrosis [63]. As mentioned earlier, the activation of the TGF-β pathway mediates collagen synthesis, promotes tissue fibrosis, and plays an important role in late radiationinduced cardiac toxicity.…”
Section: Igf-1 and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The history of traditional herb medicine dates back to a long time ago, however, during the recent decades owing to the considerable positive impacts of herbals (Aliasgharzadeh et al, ; Farhood et al, ; Mortezaee et al, ; Najafi et al, ; Shabeeb et al, ) and noticeable side effects of chemical drugs, much attention has been made in pharmacognosy (Farhood et al, , , , ; Najafi et al, ). In other words, the harmful effects of synthetic drugs lead to the substitution of natural compounds for the remediation of a number of disorders (Azmoonfar et al, ; Farhood et al, ; Kolivand et al, ; Shabeeb et al, ). It has been shown that natural compounds derived from fruits and vegetables have various biological and therapeutic activities such as anticancer, antidiabetic, antiobesity, anti‐inflammatory, and antioxidant (Amini et al, , ; Najafi et al, , ; Shabeeb et al, ).…”
Section: Introductionmentioning
confidence: 99%